The Giraffe and the Pelly and me - Dahl, Roald; Blake, Quentin (New York, NY : Puffin Books, 2013)
A small boy with a desire to own a candy shop meets a window-washing team composed of a giraffe, a pelican, and a monkey and together they go to work for the wealthy Duke of Hampshire, who makes all their dreams come true.
Keywords: Giraffes -- Fiction; Pelicans -- Fiction; Children's fiction